Book Reviews: (Historia, 2021)
1. W . Finaughty: The Recollections of an Elephant Hunter 2. T . Jeal: Livingstone 3. G. M. Trevelyan: England in the Age of Wycliffe 4. H. M. Hole: The Jameson Raid  5. C. Brooke: The Structure of Medieval Society6. G. A. Hodgett: A Social and Economic History of Medieval Europe7. O. H. Spohr: W. H. C. Lichtenstein: Foundations of the Cape 8. J. H. Davidson: South Africa, by Anthony Trollope9. D. Clammer: The Zulu War  10. J. Vansina: Oral Tradition11. B. Barlow: The Life and Times of President Brand12. A. W. Coates: The Classical Economists13. D. C. Coleman: Revisions in Mercantilism